Comparative Economic and Experimental Assessment of Air Source Heat Pump and Gas-Fired Boiler: A Case Study from Turkey - KUL, ÖNDER; UĞURAL, MEHMET NURETTİN (MDPI, 2022)
Since sustainability has become a major concern in the construction industry, making economically efficient investment decisions in energy conservation are needed to minimize energy consumption for space heating and cooling. Although Air-Source Heat Pump (ASHP) systems are used to meet buildings' heating and cooling demands worldwide, high initial setup costs limit the widespread use of these systems. This paper presents comparative assessment of ASHP system versus conventional gas-fired boiler system for a real commercial building with a floor area of 2500 m(2) in Istanbul, Turkey. The key performance variable, Coefficient of Performance (COP), of the ASHP system was experimentally evaluated. The experimental results revealed that the system's COP ranged from 3.22 to 4.32, while the outside temperature ranged from 4.8 to 18.6 degrees C and the supply water temperature ranged from 32.2 to 36.2 degrees C. Moreover, the economic analysis results showed that despite the high initial cost, ASHP systems are cost competitive against gas-fired boiler in Turkey. ASHP system could reduce the present value of total Life-Cycle Cost (LCC) by up to 26.4% (47,865 USD) compared to the conventional gas-fired boiler system because it can dramatically reduce the energy consumption per year.
Keywords: Heat Pump; Radiant Heating; Life Cycle Cost; Construction Management; Project Management